The educational preparation of nurses in a developing economy and patient mortality. (2nd March 2018) - Mahfoud, Z. R.; Gkantaras, I.; Topping, A. E.; Cannaby, A. M.; Foreman, B.; Watson, R.; Thompson, D. R.; Gray, R.
Abstract : Background: Most studies have reported that higher levels (baccalaureate degree) of educational attainment by nurses are associated with lower levels of patient mortality. Researchers working in developed economies (e.g. North America and Europe) have almost exclusively conducted these studies. The value of baccalaureate nurse education has not been tested in countries with a developing economy. Method: A retrospective observational study conducted in seven hospitals. Patient mortality was the main outcome of interest. Anonymized data were extracted from nurses and patients from two different administrative sources and linked using the staff identification number that exists in both systems. We used bivariate logistic regression models to test the association between mortality and the educational attainment of the admitting nurse (responsible for assessment and care planning). Results: Data were extracted for 11 918 (12, 830 admissions) patients and 7415 nurses over the first 6 months of 2015. The majority of nurses were educated in South Asia and just over half were educated to at least bachelor degree level. After adjusting for confounding and clustering, nurse education was not found to be associated with mortality. Implications for nursing and health policy: Our observations may suggest that in a developing economy, the academic level of nurses' education is not associated with a reduction in patient mortality. Findings should be interpreted with considerable caution but do challenge widely held assumptions about the value of baccalaureate‐prepared nurses. Further research focused on nursing education in developing economies is required to inform health policy and planning.